2020
DOI: 10.1371/journal.pone.0232550
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of knowledge of pregnancy danger signs in Indonesia

Abstract: IntroductionThe maternal mortality rate in Indonesia is still quite high. It requires good knowledge for early prevention. The study aimed to analyze the determinants of knowledge of the pregnancy danger signs in Indonesia. MethodsThe samples used were 85,832 women of childbearing age (15-49 years old). The variables included understanding of danger signs of pregnancy, types of residence, age, education, employment, marital status, wealth, parity, the autonomy of health, current pregnancy status, and media exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
79
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 24 publications
5
79
2
7
Order By: Relevance
“…This nding shows that different education levels among married female adolescents from different ethnic groups do not contirbute to give a signi cant impact on physical readiness for pregnancy. The results of this study are contradictory to some previous studies which found that education level was a positive predictor of many health outputs (30)(31)(32).…”
Section: Discussioncontrasting
confidence: 99%
“…This nding shows that different education levels among married female adolescents from different ethnic groups do not contirbute to give a signi cant impact on physical readiness for pregnancy. The results of this study are contradictory to some previous studies which found that education level was a positive predictor of many health outputs (30)(31)(32).…”
Section: Discussioncontrasting
confidence: 99%
“…Higher education level is known to be the main positive determinant of program performance in the health sector as indicated in several previous studies [33][34][35] . Otherwise, lower levels of education were found to be a barrier to program performance in the health sector 36,37 .…”
Section: Discussionmentioning
confidence: 87%
“…Husbands living in urban areas have a better chance of husband's involvement in ANC visits among the poor in Indonesia. This condition is possible because couples who live in urban areas have the opportunity to be exposed to better health information than couples who live in rural areas 34,38 .…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are in line with several previous studies in various countries, which found that a better level of maternal education is a protective factor for LBW 16,26,33 . In several previous studies, it has often been found that a better level of education results in better output on health outcomes [34][35][36][37] . On the other hand, poor education is a barrier to achieving health status to become more qualified 38,39 .…”
Section: Discussionmentioning
confidence: 99%